A new species of Gastrochilus and new records for the orchids of Nepal - Raskoti, Bhakta Bahadur (Phytotaxa, 2015)
Gastrochilus nepalensis, a new species of orchids from central Nepal is described. A key to its allied species is provided. Thirteen species are reported as new records for Nepal: Epipogium japonicum, Goodyera nankoensis, Habenaria davidii, Habenaria wolongensis, Herminium chloranthum, Herminium kamengense, Herminium longilobatum, Herminium pusillum, Liparis campylostalix, Peristylus calcaratus, Platanthera stenochila, Platanthera roseotincta, Platanthera yadongensis.